Schwannoma of the Greater Superficial Petrosal Nerve: An Unusual Site for a Common Tumor - Uppar, Alok Mohan; Rao, Shilpa; Prasad, Chandrajit; Arimappamagan, Arivazhagan; Santosh, Vani (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Greater superficial petrosal nerve (GSPN) schwannoma is a rare clinical entity. It forms a small subset of the larger group of facial nerve schwannomas. A thorough literature search yielded only 27 such cases reported to date in the English literature. We present one such rare case of GSPN schwannoma and discuss the clinical spectrum and management along with a review of the literature. We demonstrate the surgical steps in an operative video.
Keywords: greater superficial petrosal nerve; schwannoma; neurinoma; facial nerve schwannoma